2012
DOI: 10.1371/journal.pone.0046414
|View full text |Cite
|
Sign up to set email alerts
|

Earliest Porotic Hyperostosis on a 1.5-Million-Year-Old Hominin, Olduvai Gorge, Tanzania

Abstract: Meat-eating was an important factor affecting early hominin brain expansion, social organization and geographic movement. Stone tool butchery marks on ungulate fossils in several African archaeological assemblages demonstrate a significant level of carnivory by Pleistocene hominins, but the discovery at Olduvai Gorge of a child's pathological cranial fragments indicates that some hominins probably experienced scarcity of animal foods during various stages of their life histories. The child's parietal fragments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 50 publications
0
32
0
2
Order By: Relevance
“…Harvesian canals increase significantly with age whereas lacuna porosity decreases slightly (Martin, 1984;Wang and Ni, 2003). There are pathologies such as anemia (Domínguez-Rodrigo et al, 2012), syphilis (Lopes et al, 2010), leprosy (Roffey and Tucker, 2012), or co-deficiency of vitamin C and B 12 (Walker et al, 2009) well known for their impact on bone porosity. Furthermore, bone pores may be modified, also, by postmortem thermal treatments (Bosch et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Harvesian canals increase significantly with age whereas lacuna porosity decreases slightly (Martin, 1984;Wang and Ni, 2003). There are pathologies such as anemia (Domínguez-Rodrigo et al, 2012), syphilis (Lopes et al, 2010), leprosy (Roffey and Tucker, 2012), or co-deficiency of vitamin C and B 12 (Walker et al, 2009) well known for their impact on bone porosity. Furthermore, bone pores may be modified, also, by postmortem thermal treatments (Bosch et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The portrayal of particularly short and stressful lives for children has become increasingly insupportable, with evidence arguing against interpretations of rapid development (Rosas et al 2017), frequent trauma (Estabrook 2009) and excessive dietary stress (Dobrovolskaya 2014). Episodes of stress are not exceptional in human evolution for example, as reflected in other hominins which show evidence of mortality due to nutritional deficiency (Domínguez-Rodrigo et al 2012). The treatment of Neanderthal children in death also offers a picture of considerable care, far from previous views of infants simply being 'dumped' (e.g.…”
Section: )mentioning
confidence: 99%
“…Deformities on the bones suggested that the child had died from porotic hyperostosis, a condition thought to result from a deficiency in vitamin B12 -found exclusively in animal-derived foods. Humans started eating dairy products only in the past 5,000 years, meaning that the child had almost certainly died from a lack of meat 7 . So, by at least 1.5 million years ago, says Domínguez-Rodrigo, humans had become so adapted to eating meat that without it they would die.…”
Section: Meat In the Brainmentioning
confidence: 99%